Driving SME Performance through Digital and Network Capabilities: The Mediating Role of Innovation - Nuning Sri Ayu Widiarti; Chritina Whidya Utami; Denny Bernardus (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the era of digital transformation, small and medium enterprises (SMEs) are required to enhance their innovation capacity and adapt to digital platform capabilities to remain competitive. This study aims to investigate the relationship between entrepreneurial SME performance, innovation capability, network capability, and digital platform capability. Using a quantitative approach, data were collected from 278 SMEs in Indonesia through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that entrepreneurial SME performance positively influences innovation capability and network capability. Furthermore, innovation capability significantly enhances both network capability and digital platform capability. However, digital platform capability is not directly influenced by entrepreneurial performance, indicating the mediating role of innovation. The findings also highlight the interdependence between innovation and network capability in strengthening digital capabilities. This study concludes that innovation plays a key mediating role in linking business performance to digital transformation. Practical implications suggest that SMEs must foster a culture of innovation and invest in digital skills and networking strategies. Theoretically, the study enriches the understanding of dynamic capabilities and digital transformation in the SME context.